2017
DOI: 10.15761/cmid.1000122
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium goodii Related Breast Implant Infection: First Case and Literature Review

Abstract: A 46-year-old Caucasian female was diagnosed with invasive lobular carcinoma of the left breast. She underwent mastectomy and placement of a silicone breast implant as a single-stage procedure. Two weeks after surgery, she developed erythema and drainage to the postoperative site, necessitating removal of the breast implant. Operative cultures grew Mycobacterium goodii. She was successfully treated with a three month course of moxifloxacin and doxycyline. M. goodii should be in the differential of postoperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…They reviewed 13 cases, and none of them were breast infections or implant-related breast infections. In 2017, Pandita et al 4 reported the first case of an M. goodii –related breast implant infection along with literature review. Their patient had a history of invasive lobular carcinoma of the left breast and developed erythema and drainage to the postoperative site 2 weeks after mastectomy and placement of a silicone breast implant as a single-stage procedure.…”
Section: Discussionmentioning
confidence: 99%
“…They reviewed 13 cases, and none of them were breast infections or implant-related breast infections. In 2017, Pandita et al 4 reported the first case of an M. goodii –related breast implant infection along with literature review. Their patient had a history of invasive lobular carcinoma of the left breast and developed erythema and drainage to the postoperative site 2 weeks after mastectomy and placement of a silicone breast implant as a single-stage procedure.…”
Section: Discussionmentioning
confidence: 99%
“…3 M. goodii has been associated with soft tissue infection, osteomyelitis, bursitis, pneumonia, and achalasia- associated pulmonary disease. 1,4,5 Cases of M. goodii infections have also been reported to complicate a variety of surgical procedures and devices, including; hardware, 1,2 pacemaker devices, 1,6 mitral valve annuloplasty, 7 prosthetic heart valves, 8 deep brain stimulators, 9 intra-opthalmic devices, 10 intra-abdominal mesh, 2 ventriculoperitoneal shunts, 11 breast implants, 12 and intravenous catheters. 4 In the majority of these cases involving prosthetic material, clearance of the infection was only achieved by removal of foreign material and administration of antibiotic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Most M. goodii isolates are susceptible to trimethoprim/sulfamethoxazole, ciprofloxacin, doxycycline, imipenem and amikacin 7. Although rare, one other M. goodii infection associated with a breast implant was reported in 2017 8. Additionally, a recent M. goodii infection associated with reduction mammoplasty was reported 7.…”
Section: Descriptionmentioning
confidence: 99%
“…As presentations with this organism are rare, it is unclear what the typical presentation of infected breast expanders is. Reported cases have used at least 3–6 months of combination or monotherapy for deep-seated infections, depending on the situation 5–8…”
Section: Descriptionmentioning
confidence: 99%